Malignant Tumor Formation After Transplantation of Short-Term Cultured Bone Marrow Mesenchymal Stem Cells in Experimental Myocardial Infarction and Diabetic Neuropathy - Jin‐Ok Jeong; Ji Woong Han; Jin‐Man Kim; Hyun‐Jai Cho; Changwon Park; Nam-Ho Lee; Dong‐Wook Kim; Young‐sup Yoon (2011)
Bone marrow (BM)-derived mesenchymal stem cells (MSCs) hold great promise for cardiovascular cell therapy owing to their multipotency and culture expandability.The aim of the study was to investigate whether MSCs can treat experimental acute myocardial infarction (MI) and diabetic neuropathy.We isolated mononuclear cells from mouse BM and cultured MSCs in a conventional manner. Flow cytometry analyses of these cultured cells at passage 4 showed expression of typical MSC markers such as CD44 and CD29, but not hematopoietic markers such as c-kit, flk1, and CD34. To determine the therapeutic effects of MSCs, we injected MSCs into the peri-infarct area after ligation of the left anterior descending coronary arteries of mice and, as separate experiments, injected the same batch of MSCs into hindlimb muscles of mice with diabetic neuropathy. During the follow-up at 4 to 8 weeks after cell transplantation, growing tumors were observed in 30% of hearts in the MI model, and in 46% of hindlimbs in the diabetic neuropathy model. Histological examination of the tumors revealed hypercelluarity, pleomorphic nucleoli, cytological atypia and necrosis, and positive staining for α-smooth muscle actin, indicative of malignant sarcoma with myogenic differentiation. Chromosomal analysis of these MSCs showed multiple chromosomal aberrations including fusion, fragmentation, and ring formation.Genetically unmodified MSCs can undergo chromosomal abnormalities even at early passages and form malignant tumors when transplanted in vivo. These results suggest that careful monitoring of chromosomal status is warranted when in vitro expanded MSCs are used for cell therapy such as for MI.